INVESTIGASI KEBERADAAN DAN KETERKAITAN UNSUR KELUMIT PADA BATUBARA FORMASI MANUMBAR PIT Y-2 DI CEKUNGAN KUTAI, KALIMANTAN TIMUR - Gibran, Akhmad Khahlil; Prasetyo, Ezza Ray Raditya; Purwasatriya, Eko Bayu; Mulyanto, Didik Jati (Jurnal Teknologi Mineral dan Batubara, 2025)
The Kutai Basin, renowned as a coal-bearing basin, ranks among the largest basins in Indonesia. Coal consists of various constituents, including major elements, trace elements, macerals, mineral impurities, and other components. The purpose of this research is to conduct a more in-depth analysis of the content of coal, with a specific focus on trace components. This study aimed to investigate the features, potential, enrichment of trace elements, and their correlation with the total sulfur and ash content in coal. An examination using ICP-OES (Inductively Coupled Plasma – Optical Emission Spectrometer) was conducted on 11 coal seams from Y-2 PIT. This analysis aimed to identify the level of trace elements, main elements, total sulfur, and ash content in the coal. The study's findings revealed that the elements' distribution and characteristics on the chemostratigraphy analysis chart were categorized into five distinct features, subsequently represented as chemozone. Moreover, it is established that the area with the highest potential is chemozone 3, where all trace elements undergo substantial enrichment within this region. It is well-established that several trace elements exhibit a positive correlation with changes in the overall sulfur and ash content of coal. The trace elements shown to be positive correlation linked to variations in the overall sulfur level are Cd, Mn, and Pb. On the other hand, the elements Cr, Cu, Pb, and V are tied positive correlation with changes in the ash content value. This study expands our understanding of the distribution and concentration of trace elements in coal from Indonesia's largest coal producing area. This data can be utilized to create more precise geochemical and stratigraphic models in the future.